In Vivo Evaluation of [Gly14]-Humanin’s Protective Effect Against Cisplatin-Induced Ototoxicity - Yaşar, Murat; Gökmen, Sedat; Atalay, Fatma; Çınar, İrfan and Aydin, Yusuf and Tatar, Musa (The European Research Journal, 2026)
Objectives: This study aimed to evaluate in vivo the potential protective effects of [Gly14]-humanin against cisplatin-induced ototoxicity (CIO) and its modulatory effects against oxidative stress, inflammatory, and apoptotic markers Methods: Thirty-five male Balb/c mice were randomly divided into five groups: control, cisplatin, cisplatin + [Gly14]-humanin (3 mg/kg), cisplatin + (6 mg/kg), and vitamin E. Cisplatin (10 mg/kg, b.w.) was administered as a single dose. [Gly14]-humanin was administered intraperitoneally for 14 days. Biochemical analyses (Superoxide dismutase (SOD), glutathione (GSH), and malondialdehyde (MDA)), gene expression levels (TNF-α, IL-1β, IL-6, CASP-3, CASP-9, Bcl-2/Bax), and histopathological examinations (PARP1, PARP2 immunoreactivity) were performed in cochlear tissue samples to evaluate oxidative stress, inflammation, and apoptosis. Results: Cisplatin decreased SOD and GSH levels and increased MDA levels in the cochlear tissue (P<0.05). With the application of [Gly14]-humanin, these parameters approached their normal levels. Cisplatin increased the values of pro-inflammatory and pro-apoptotic markers (TNF-α, IL-1β, IL-6, Caspase-3 (CAS-3), Caspase-9 (CAS-9)) significantly while reducing the Bcl-2/Bax ratio (P<0.05). [Gly14]-humanin administration reversed these effects in a dose-dependent manner. Histological analysis also revealed decreased PARP1 and PARP2 immunoreactivity in [Gly14]-humanin treated groups, comparable to the positive control (vitamin E). Conclusions: The findings of this study show that [Gly14]-humanin exhibits important protective effects against CIO by attenuating oxidative stress, inflammation, and apoptosis in cochlear tissues. Further studies evaluating the clinical efficacy and reliability of [Gly14]-humanin are now needed.